(untitled) (Swiss Medical Weekly, 2018)
Open Access (OA) is widely considered a breakthrough in the history of academic publishing, rendering the knowledge produced by the worldwide scientific community accessible to all. In numerous countries, national governments, funding institutions and research organisations have undertaken enormous efforts to establish OA as the new publishing standard. The benefits and new perspectives, however, cause various challenges. This essay addresses several issues, including that OA is deeply embedded in the logic and practices of data capitalism. Given that OA has proven an attractive business model for commercial publishers, the key predictions of OA-advocates, namely that OA would liberate both scientists and tax payers from the chains of global publishing companies, have not become true. In its conclusion, the paper discusses the opportunities and pitfalls of non-commercial publishing.